2017
DOI: 10.1016/j.proci.2016.06.164
|View full text |Cite
|
Sign up to set email alerts
|

Investigations of microwave stimulation of a turbulent low-swirl flame

Abstract: Irradiating a flame by microwave radiation is one of several Plasma-Assisted Combustion (PAC) technologies that can be used to modify the combustion chemical kinetics in order to improve flame-stability and to delay lean blow-out. One practical implication is that engines may be able to operate with leaner fuel mixtures and have an improved fuel flexibility capability including biofuels. In addition, this technology may assist in reducing thermoacoustic instabilities that may severely damage the engine and inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 32 publications
1
17
0
Order By: Relevance
“…Experimental details for similar conditions have been presented in a previous publication by Ehn et al, 37 and experimental data and LES were further discussed in another publication by the same group. 38 The authors presented averaged OH-and CH 2 O-PLIF data in this publication showing a distinct increase in OH-PLIF signal with microwave stimulation, as well as a broadening of the flame. Furthermore, the averaged PLIF images indicated that the flame was displaced with microwave stimulation, in that it moved closer to the burner nozzle.…”
Section: Energy and Fuelsmentioning
confidence: 95%
See 3 more Smart Citations
“…Experimental details for similar conditions have been presented in a previous publication by Ehn et al, 37 and experimental data and LES were further discussed in another publication by the same group. 38 The authors presented averaged OH-and CH 2 O-PLIF data in this publication showing a distinct increase in OH-PLIF signal with microwave stimulation, as well as a broadening of the flame. Furthermore, the averaged PLIF images indicated that the flame was displaced with microwave stimulation, in that it moved closer to the burner nozzle.…”
Section: Energy and Fuelsmentioning
confidence: 95%
“…Planar laser-induced fluorescence data from OH and CH 2 O show that the flame is shifted closer to the burner nozzle when the flame absorbs microwave energy. 38 The temperature increase and the shift in flame position indicate an increase in flame speed for the turbulent flame as microwaves are applied to the flame. Development of numerical simulation models for studying electrical aspects of flames is a broad and active research area.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The experiments also focused on turbulent flames, temperature fields at ignition, burning velocity and changes in the flame position under pulsed microwave input. [6] Ju et al made a sensitivity analysis of the free electron number for different equivalence ratios. Their results indicated that the exhaust gas could possibly absorb the majority of the microwave electron heating.…”
Section: Introductionmentioning
confidence: 99%